Molecular detection of Haemonchus contortus on spotted deer (Axis axis) - Arif, Ridi; Mifthadillah, Sekar Ayu; Natalie, Gabriella (ARSHI Veterinary Letters, 2025)
Spotted deer (Axis axis) as a protected endemic animal has the potential to be developed to provide economic value. However, in general, deer are often infected by endoparasitic diseases caused by various factors such as direct contact with infected areas to transmission through feed. As a result of endoparasitic infections, infected animals can experience malnutrition, physiological disorders, and even death. This study aims to identify nematode worm species using molecular diagnosis in spotted deer. Molecular identification of nematode species in deer feces was carried out by fecal sample collection and cultivation, larvae isolation, DNA extraction, PCR process, and electrophoresis. Molecular analysis using specific primer targeting the ITS gene. The PCR results showed the single band at 260 bp. Based on the result, the nematode species that has infected the spotted deer was Haemonchus contortus. These findings provide the first molecular-level confirmation of endoparasite infection in spotted deer in Indonesia, expanding the existing diagnostic information for wildlife health monitoring.